2023
DOI: 10.1126/scitranslmed.abn3464
|View full text |Cite
|
Sign up to set email alerts
|

Single immunizations of self-amplifying or non-replicating mRNA-LNP vaccines control HPV-associated tumors in mice

Abstract: As mRNA vaccines have proved to be very successful in battling the coronavirus disease 2019 (COVID-19) pandemic, this new modality has attracted widespread interest for the development of potent vaccines against other infectious diseases and cancer. Cervical cancer caused by persistent human papillomavirus (HPV) infection is a major cause of cancer-related deaths in women, and the development of safe and effective therapeutic strategies is urgently needed. In the present study, we compared the performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 83 publications
2
40
0
1
Order By: Relevance
“…Conversely, irrelevant mRNA lacking HPV antigen expression failed to induce the suppression of tumor growth, as demonstrated by other research studies. 19,41 Thus, mHTV is expected to exert therapeutic effects in the patients infected with HPV types 16 and 18 and show preventive effects against the progression of precancerous lesions. 42 Currently, DNA vaccines are the most widely used vaccines that have been proven to be effective in clinical trials (NCT01634503, and NCT00788164).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, irrelevant mRNA lacking HPV antigen expression failed to induce the suppression of tumor growth, as demonstrated by other research studies. 19,41 Thus, mHTV is expected to exert therapeutic effects in the patients infected with HPV types 16 and 18 and show preventive effects against the progression of precancerous lesions. 42 Currently, DNA vaccines are the most widely used vaccines that have been proven to be effective in clinical trials (NCT01634503, and NCT00788164).…”
Section: Discussionmentioning
confidence: 99%
“…169 Additionally, vaccination with self-amplifying mRNA of three HPV antigens has shown efficacy in eradicating subcutaneous HPV+ tumors at various stages and preventing their relapse. 170 A previous study has shown that HPV vaccination for the treatment of cervical cancer using a traditional vaccine was most effective when combined with the chemotherapeutic agent cisplatin. 171 As such, future mRNA LNP vaccines may incorporate a combinatorial treatment strategy with traditional chemotherapeutics.…”
Section: Mrna Lnps For Sti Vaccinationmentioning
confidence: 99%
“…One study showed that such HPV vaccination activated antigen-specific effector cells to attack subcutaneous HPV+ tumors, and circulating memory CD8 + T cells protected from relapse . Additionally, vaccination with self-amplifying mRNA of three HPV antigens has shown efficacy in eradicating subcutaneous HPV+ tumors at various stages and preventing their relapse . A previous study has shown that HPV vaccination for the treatment of cervical cancer using a traditional vaccine was most effective when combined with the chemotherapeutic agent cisplatin .…”
Section: Localized Delivery Of Rna For Women’s Healthmentioning
confidence: 99%
“…100 While these DCs truly recapitulate features and functions of in vivo cDCs, the yield remains low, limiting their widespread use for vaccination purposes. With new technologies emerging to target cDCs in vivo using antibody-based strategies 7 or lipid nanoparticles (LNPs) as carriers to deliver tumor antigens to DCs, 101,102 in vivo targeting might become the preferred strategy for DC vaccination purposes. Broadly speaking, immunogenicity is determined by a combination of two properties: antigenicity and adjuvanticity.…”
Section: Box 1 DC Subsets In Vivo and In Vitromentioning
confidence: 99%